2022
DOI: 10.3233/jad-220438
|View full text |Cite
|
Sign up to set email alerts
|

Digital Technologies to Prevent Social Isolation and Loneliness in Dementia: A Systematic Review

Abstract: Background: Dementia poses significant and sustained challenges to global society. Diagnosis can lead to increased feelings of loneliness and social isolation. People with dementia living alone are particularly at risk. Considering the growing number of technologies proposed to aid people with dementia address social isolation and loneliness, we reviewed the existing literature.Objective: To collate and summarize current evidence for digital technologies to prevent social isolation and loneliness for people wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 30 publications
0
23
0
Order By: Relevance
“…From 50 of the included studies, the following were used to promote autonomy: patient monitoring [25], [38], [39], [46], [50], [51], [61], [93]–[95], [100], [101], [103], [105]–[108], [111], [120]–[123], [125], [132], [137], [141], care support [53], [95] and digital therapeutics [21], [22], [25], [30], [32], [33], [38], [39], [49]–[51], [53], [56], [60], [61], [64], [70], [80]–[82], [86], [91], [93]–[95], [100], [104], [105], [107], [109]–[111], [114], [123], [125], [131], [138], [141]. Resilience was also mentioned as a significant factor contributing to enhanced autonomy [41], [62], [129], [130].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…From 50 of the included studies, the following were used to promote autonomy: patient monitoring [25], [38], [39], [46], [50], [51], [61], [93]–[95], [100], [101], [103], [105]–[108], [111], [120]–[123], [125], [132], [137], [141], care support [53], [95] and digital therapeutics [21], [22], [25], [30], [32], [33], [38], [39], [49]–[51], [53], [56], [60], [61], [64], [70], [80]–[82], [86], [91], [93]–[95], [100], [104], [105], [107], [109]–[111], [114], [123], [125], [131], [138], [141]. Resilience was also mentioned as a significant factor contributing to enhanced autonomy [41], [62], [129], [130].…”
Section: Resultsmentioning
confidence: 99%
“…The topic of engagement and social interaction was highlighted in 64 studies. They differentiated between cases where DATs increased social interaction [20], [28], [29], [34], [35], [38], [41], [45], [54], [59], [64], [70], [72], [80], [82], [83], [85], [100], [102], [112], [113], [123], [129], [131], [133], [134] and fostered higher engagement (i.e., in therapy settings) [23], [26], [29], [34], [36]–[38], [40]–[42], [45], [53]–[55], [57], [60], [62], [63], [66]–[68], [70], [73], [76]–[79], [84], [85], [87], [88], [90], [91], [96], [100], [109], [112], [114], [116], [118], [122], [127], [130], [131], [133], [135], [136], [138], [139], [141].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Indigenous communities, Walker et al (2020) found that noting culture as a source of strength (OR = 0.514) was associated with lower risk of ADRD, though these results were not significant statistically. (Neal et al, 2021;Rai et al, 2022), while one included older people without ADRD (Heins et al, 2021). The eight articles are subdivided into (A) five on technology-based social interventions (Heins et al, 2021;Hirt et al, 2021;Neal et al, 2021;Pinto-Bruno et al, 2017;Rai et al, 2022), (B) two on other social interventions (Marks and McVilly, 2020;Scott et al, 2022), and (C) one on mixed technology-based and other social interventions (Han et al, 2016) ○ In one study, VR headset with handheld controllers resulted in increased participation in social activities.…”
Section: Includedmentioning
confidence: 99%